Composition, electric-field and temperature induced domain evolution in lead-free Bi0.5Na0.5TiO3-BaTiO3-SrTiO3 solid solutions by piezoresponse force microscopy. (October 2016) - Liu, Dan; Tian, Chengyue; Ma, Chuanguo; Luo, Laihuo; Tang, Yanxue; Wang, Tao; Shi, Wangzhou; Sun, Dazhi; Wang, Feifei
Abstract: In order to clarify the nanoscale mechanism responsible for the large strain response in Bi0.5 Na0.5 TiO3 -BaTiO3 -SrTiO3 (BNBST) reported in our previous work, the composition, electric-field and temperature induced domain evolution was investigated. Results indicated the increase of the SrTiO3 concentration led to the evolution from non-ergodic relaxor ferroelectric domain to ergodic relaxor state. The in-situ poling results indicated the transition from the ergodic relaxor to ferroelectric was induced under sufficient high electric field in BNBST with high strain response, which was suggested as the main reason for the large strain level. The temperature-dependent domain evolution was also characterized and discussed. Graphical abstract: